The role of frames in shaping the representation of local knowledge and concerns in scientific texts - Roos, Roxana (Frontiers in Climate, 2024)
Research teams working with indigenous people or local communities in the field of global environmental change represent local knowledge and concerns related to climate or environmental issues in the resulting scientific texts. However, by highlighting some aspects in particular ways and fading others to the background, every representation simultaneously reveals, conceals, and distorts aspects of what is represented. This paper aims to analytically highlight how frames in scientific texts are at work in emphasizing some aspects of local knowledge and concerns while fading other aspects into the background, which inevitably has micro and macro consequences through how local knowledge is incorporated, represented, and added to the body of knowledge of a given field. I have adapted a widely used frame concept from media studies to make it suitable for the analysis of scientific texts. The proposed method identifies main frames of a paper, maps how devices for achieving selective emphases, such as repetitive formulations and strong words, are at work in the text, and elicits how the frame's key functions occur in papers: (1) identify problems, (2) diagnose causes, (3) make moral judgments, (4) suggest solutions or offer a path toward solutions, and (5) attribute roles. Points (4) and ( 5) are specifically designed for the analysis of scientific texts. In addition, I have added a step that shows how frames shape representations of local knowledge and concerns in scientific texts. This method is meant to develop reflexive awareness among the scholarly community about their writing practices and promote critical thinking about the unintended impacts that uncritical reproduction of taken-for-granted frames may have through their shaping of representations of local and indigenous knowledge and concerns. To illustrate the potential of the frame concept for analyzing scientific texts, I applied the new method to two papers. Further, the paper discusses the potential of frame analysis as a tool for reflexivity among research teams that work with and within local communities.